Review on Certain Aspects of Co-operative Movement in India - Planning Commission (Planning Commission, Government of India, 1957)
Sir Malcolm Darling’s Report on Certain Aspects of Co-operative Movement in India, prepared after an extensive field visit during the Second Five-Year Plan (1956–1961), offers a critical appraisal of the agricultural cooperative sector and presents a structured roadmap for its sustainable expansion. While acknowledging the Plan’s ambitious targets—including a substantial increase in agricultural credit, expansion of cooperative societies, and growth in membership—Darling cautions against rapid enlargement without strengthening foundational thrift and credit societies that form the backbone of rural cooperation. The report highlights serious concerns regarding overdue loans, liberal lending practices, inadequate supervision, and insufficient training of cooperative officials, particularly registrars and field personnel. Emphasis is placed on disciplined credit expansion, promotion of thrift habits among cultivators, and safeguarding cooperative autonomy from excessive governmental interference. Darling advocates a robust and systematic training framework incorporating field-based learning, refresher courses, and cooperative education in regional languages, alongside continuity in administrative leadership to ensure institutional stability. He also recommends cautious introduction of new cooperative forms, improved liaison between central and state authorities, restructuring of large and small societies for viability, and refined financial practices to maintain liquidity and accountability. Addressing socio-cultural factors influencing rural indebtedness, the report underscores the importance of community engagement and educational innovation in fostering cooperative values. Overall, Darling’s analysis stresses gradual, well-supervised growth, professional capacity building, and grassroots empowerment as essential prerequisites for transforming the cooperative movement into an effective instrument of rural development and peasant welfare in India.
Government of India Planning Commission New Delhi, 1957
Keywords: Co-Operative Movement in India; Sir Malcolm Darling Report; Second Five-Year Plan 1956–61; Agricultural Credit Expansion; Thrift and Credit Societies; Rural Cooperative Banking; Cooperative Training Framework; Registrar Capacity Building; National Extension Service Review; Overdue Loan Management; Grassroots Cooperative Strengthening; Cooperative Education Reform